The sugarhouse blues - Stewart, Mariah (Stewart, Mariah. Hudson sisters novel, 2018)
"As strangers linked only by their DNA try to become a family, the Hudson sisters also try to come to terms with the father they only thought they knew. In the process, each woman discovers her own capacity for understanding, forgiveness, love, and the true meaning of family"--